Los ecos del darwinismo en España a través de la literatura. Escritores y escritoras - Pilar Díaz Sánchez (Investigaciones Feministas, 2009)
This article analyses the reception of the theories of evolution, Darwin’s in particular, through 19th century Literature in Spain. It points at the role of women writers and their construction of models of womanhoodand establishes a difference between male and female roles. We present the relationship between positivism, naturalism and Darwinism, and the defense of abolitionism in women’s Literature. Special reference is given to Emilia Pardo Bazán in this respect.